Green Innovation, Corporate Environmental Ethics, and Competitive Advantages of Chinese Automobile Industry During COVID-19: Corporate Environmental Management as Moderator - Wu, Wenhan; Wu, Wenzhuo; Wu, Kouhua; Ding, Chen; Fan, Chenya (Frontiers in Psychology, 2022)
Objective The main purpose of this study is to investigate the impact of green product and process innovation on the competitive advantages of the Chinese automobile industry during coronavirus disease 2019 (COVID-19). This study also examined the mediating role of corporate environmental ethics (CEE) and the moderating role of corporate environmental management in the relationship between the green product and process innovation on the competitive advantages of the Chinese automobile industry during COVID-19. Methods This study used a quantitative approach of research with the cross-sectional method for the collection of data. This study also used purposive sampling for the collection of data from the production managers of the automobile industry of China. The structural equation modeling-partial least squares (SEM-PLS) is used to analyze the data. Results The results of direct effects indicated that green product innovation has a significant and positive effect on the corporate advantages (β = 0.294, t = 2.868) and green process innovation also has a significant and positive effect on the corporate advantages (β = 0.350, t = 3.276). Moreover, green product innovation has also a significant effect on corporate advantages (β = 0.334, t = 4.258) and green product innovation has also a significant effect on corporate advantages (β = 0.269, t = 3.202). Significance The research in this domain about the antecedents of green innovation is still minimal in the previous literature. One of the antecedents of the green innovation, corporate environmental ethics is discussed in this study; thus, it provides the understanding of green innovation as the mediator which would mediate the relationship between corporate environmental ethics and competitive advantage in the auto manufacturing industry of China. Novelty This study is among very few to examine the relationship between green innovation, corporate environmental ethics, corporate environmental management, and competitive advantages of the Chinese automobile industry during COVID-19.